Use of microalgae for the removal of environmental pollutants - Usmani, Mursaleen; Sultana, Hafsa (International Journal of Scientific World, 2014)
In this mini review it is to focus that how can pollutants be removed from the environment by utilizing microalgae which are deliberately increasing and causing hazardous effects to our environment. Microalgae are sunlight-driven cell factories that convert carbon dioxide to potential biofuels, foods, feeds and high-value bioactives. Various types of pollutants continuously causing damage to the environment and after a long-term observation it is found that there is a best option of using microalgae in different techniques for reducing environmental pollutants. Since, versatile species of microalgae has been a part in reduction and removal of environmental pollutants as we observed in different bioremmedial techniques such as in waste water treatment plants, heavy metal removal techniques, bio-degradation of azo-dyes, phenol and other organic aromatic compounds which are dangerous to the environment. It is reappraised that one of microalgae specie which is named as chlorella vulgaris is found to be very effective in removing of heavy metals, waste water treatment and also in biodegradation of azo-dyes. This article basically explained the usefulness of using microalgae for the remediation of pollutants.